PENYULUHAN MANAJEMEN PENGELOLAAN KEUANGAN KELUARGA PADA JAMAAH RANTING AISYIAH LOWOKWARU II KOTA MALANG - Millatina, Afifah Nur; Amalia, Rahmi; Rifa’i, Mochamad Novi (Bulletin of Community Service and Development, 2025)
Purpose of the study: Good family financial management is an important foundation for achieving household economic resilience, especially for Muslim families. However, many families still lack adequate understanding and skills in planning, managing, and controlling finances effectively and in accordance with sharia principles. This community service activity aims to improve literacy and family financial management skills in the Aisyiyah Lowokwaru II Malang City branch congregation. Methodology: The activity implementation method uses a participatory approach through counseling, interactive discussions, and simple mentoring in preparing family financial budgets. The material presented includes basic concepts of family financial management, budget planning, income and expenditure management, debt control, and strengthening Islamic financial values ​​​​in everyday life. Main Findings: The results of the activity show an increase in the congregation's understanding of the importance of family financial planning, the ability to prepare simple budgets, and awareness to manage finances more wisely and directed. . Applications of this study: This activity is expected to have a sustainable impact in increasing the independence and economic well-being of Aisyiyah congregation families. Novelty/Originality of this study: The community in the Lowokwaru II Malang City branch congregation can improve their family financial management.